Hubungan Mobilisasi Dini Dengan Proses Penyembuhan Operasi Post Seksio Sesarea - Renny Adelia Tarigan; Nurul Huda (Jurnal Anestesi, 2023)
The process of healing a good cesarean section wound is the return of the former abdominal wall incision and the general recovery of the mother's condition as before. At RSHB in 2022 the number of cesarean section deliveries is 80% per 55 deliveries, a poor healing process will cause infection in the wound area so that mothers will be delayed in caring for their children. This study aims to determine the relationship between early mobilization and wound healing process by cesarean section at RSHB.This study uses analytic observation, data collection techniques using observation sheets. The population in this study were post-cesarean section mothers at RSHB, when the researcher was in April 2022. The sampling technique was accidental sampling which was carried out by meeting or visiting as many as 30 people. Data processing is done through the process of editing, coding, tabulating, scoring and analysis.The results of the study found that there were 5 people (16.65%) who did not mobilize and 20 people (66.7%) did mobilization and 5 (16.65%) people did not experience a good healing process. The result of the chi-square test has a result of 0.00, which means that Ho is rejected, Ha is accepted, so there is a significant relationship between early mobilization and the wound healing process for cesarean section surgery.The results of the study can be concluded that there is a relationship between early mobilization and the process of wound healing by cesarean section at RSHB. It is hoped that health workers will apply more early mobilization.